P027 Effects of anti-TNF and anti-α4β7 drugs on circulating monocytes migratory capacity in inflammatory bowel disease. (21st January 2022) - Soleto, I; Fernández-Tomé, S; Mora-Gutiérrez, I; Baldan-Martin, M; Ramirez, C; Santander, C; Moreno-Monteagudo, J A; Casanova, M J; Casals, F; Casabona, S; Becerro, I; Chaparro, M; et al.
Abstract: Background: Inflammatory bowel disease (IBD) is an idiopathic and chronic disorder that include ulcerative colitis (UC) and Crohn's disease (CD). Both diseases are different but show an uncontrolled intestinal immune response that generate tissue inflammation. Monocytes (Φ) play a key role in the tolerogenic maintenance in the gastrointestinal mucosa. These cells are antigen presenting cells highly specialized to control immune response against gut microbiota and food antigens. It has been previously reported that circulating Φ are recruited by intestinal mucosa in a CCR2 dependent manner. Also, in IBD patients this Φ recruitment is more prominent than in healthy controls (HC) but the specific migration mechanism is still unknown. Methods: This is a cross-sectional observational postmarketing study where the modulatory effect of different biologic treatments on samples from patients with endoscopic diagnosis of IBD and HC was studied ex vivo. Peripheral blood mononuclear cells (PBMC) were obtained from 15 patients per group, and were cultured in presence of anti-TNF or vedolizumab. Following culture, surface markers expression was determined hence assessing the differential effect of biological drugs (if any) over the Φ subset in the different groups. After that, the migratory capacity of circulating Φ toward CCL2, CCL25 and MadCam1 from the different study groups was determined. Finally, we evaluated the Φ migratory capacities in presence of biological drugs or with culture media alone. Results: Our data showed that within CD14 + population, CD patients presented a higher percentage of CCR5 + and CCR9 + and the surface expression level of CCR2 and CCR9 was increased. In addition, anti-TNF reduced the number of CCR9 + Φ subset in HC. In HC an UC patients vedolizumab reduced the percentage of β7 + Φ (Figure 1). According to the circulating Φ migratory capacity as expected, the migration towards CCL2 was higher than toward culture media (Figure 2). When the effect of biological drugs was evaluated, surprisingly anti-TNF increased the Φ migration. Also, vedolizumab showed a clear tendency to decrease the Φ migration towards CCL2 and MadCam1 in HC and in UC (Figures 3 and 4). Conclusion: Circulating Φ from IBD patients express a different migration pattern than HC, being the expression of these molecules modulated by anti-TNF drugs. The capacity of circulating Φ to migrate towards CCL2 is higher than towards culture media. Unexpectedly, anti-TNF increases the migratory capacity of Φ. On other hand, treatment of Φ from HC and UC patients with vedolizumab, induces a clear downward trend of their migratory capacity towards CCL2 and MadCam1